Sistem Pemberian Pakan Otomatis dengan Monitoring pH dan Kondisi Ikan serta Pengendali Suhu Optimal Menggunakan Fuzzy Logic Pada Aquarium - Pratama, Moh Bagus; Abdillah, Naufal (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2025)
An aquarium is an artificial ecosystem used to care for and display various types of fish and aquatic organisms. It requires special attention to critical parameters such as water temperature and pH levels to maintain the health and quality of life of the organisms within. In addition, regular feeding is an essential aspect of successful aquarium maintenance. Monitoring and regulating all these parameters is a complex task that demands continuous attention, thereby creating a need for automation solutions. Hobbyists who enjoy keeping fish and aquatic plants are often fascinated by the beauty of the ecosystems they create, yet they face difficulties in maintaining them. Many of them today are caught in routines that require them to frequently leave home, resulting in limited time for aquarium care. This situation presents a real challenge for aquarium enthusiasts. To address this problem, the concept of the Internet of Things (IoT) is applied in the development of a control and monitoring tool known as a “smart aquarium.” In this final project, a system has been developed and installed in an aquarium, enabling remote control and monitoring—providing an innovative solution for busy hobbyists. The use of automation technology in aquarium management has advanced significantly in recent years. The implementation of automatic feeding systems, pH controllers, and temperature regulation has become essential in creating a stable and balanced aquarium environment. The use of fuzzy logic to control these parameters can help improve system performance and ensure better long-term stability.